Gambaran Tingkat Pengetahuan tentang Germas pada Masyarakat Desa Sumber, Kecamatan Trucuk, Kabupaten Klaten - Triyana, Triyana; Astuti, Dwi Nur (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Non-communicable diseases in Indonesia are increasing epidemiologically. This is marked by an increase in the prevalence of non-communicable diseases such as hypertension, Diabetes Mellitus, hyperlipidemia, stroke, coronary heart disease. and increasing mortality rates. National policies related to health through the Ministry of Health of the Republic of Indonesia in order to realize a better level of public health, the government has created the Healthy Living Community Movement (GERMAS) program. It is hoped that the GERMAS program will be able to prevent the high rate of non-communicable diseases by changing the behavior of the Indonesian people regarding healthy living. Objectives: to determine the level of knowledge of the people of Sumber village, Trucuk District, Klaten Regency regarding the Healthy Living Community Movement (GERMAS). Methods: This quantitative research has a cross sectional design. The research will be carried out in April 2025 in Sumber Village, RT 19 RW 8, Trucuk District, Klaten Regency. The sampling technique uses a proportional random sampling approach with measuring instruments using a questionnaire. The statistical test that will be used is descriptive analysis. Results: The majority of people's knowledge about the Healthy Living Community Movement (Germas) in Sumber Village, Trucuk District, Klaten Regency already has good knowledge, namely 93.3%, while only 6.67% have poor knowledge about GERMAS. Conclusion: A good level of knowledge is supported by the implementation of a healthy lifestyle in daily life such as physical activity, consuming vegetables and fruit but routine checks have not been carried out Keywords : GERMAS, Knowledge, Non-Communicable Diseases